The servitization of manufacturing: a systematic literature review of interdependent trends - Lightfoot, Howard; Baines, Tim S.; Smart, Palie (Emerald Group Publishing Limited, 2013)
Purpose: The servitization of manufacturing is a diverse and complex field of research interest. The purpose of this paper is to provide an integrative and organising lens for viewing the various contributions to knowledge production from those research communities addressing servitization. To achieve this, we set out to address two principal questions, namely: (i) where are the knowledge stocks and flows amongst the research communities? and (ii) what generic research concerns are being addressed by these communities. Design/Methodology/Approach: Using an evidenced based approach, we have performed a systematic review of the research literature associated with the servitization of manufacturing. This investigation incorporates a descriptive and thematic analysis of 148 academic and scholarly papers from 103 different lead authors in 68 international peer-reviewed journals. Findings: Our work proposes support for the existence of distinct researcher communities namely; services marketing, service management, operations management, product-service systems and service science management and engineering, which are contributing to knowledge production of the servitization of manufacturing. The generic research concerns being addressed within these communities are associated with the concepts of product-service differentiation, competitive strategy, customer value, customer relationships and product-service configuration. Research limitations/implications: Our review is limited by the issues addressed in the literature by specific researcher communities and there is likely to be a wealth of literature addressing other relevant research (e.g. vertical integration, outsourcing). Therefore, immediate opportunities for future work are rooted in the limitations of our own work and in broadening our perspective of the servitization field. Originality/value: This research has further developed and articulated the identities of distinct researcher communities actively contributing to knowledge production in the servitization of manufacturing, and to what extent they are pursuing common research agendas. This study provides an improved descriptive and thematic awareness of this existing body of knowledge, allowing the field to progress in a more informed and multidisciplinary fashion.